Evaluaciòn del manejo poscosecha del cacao (Theobroma Cacao. L), en el Cantón El Pangui, provincia de Zamora CHinchipe - Ávila Pintado, Moraima Azucena (2020)
The production and marketing of cocoa at the country level constitutes one of the most important items within the economies not only of large producers but of medium and small producers located throughout the country: coast, mountains and east. The province of Zamora Chinchipe has the climate (temperature, relative humidity, environmental biodiversity, among others) that would be considered as comparative advantages for the production of quality cocoa. The present work, in the diagnosis made, identifies a series of shortcomings in the post-harvest handling of the product itself that not only require management solutions of the fruit already harvested but also of the technical-productive reorientation at the level of the cocoa production units, specifically In the production process. Post-harvest technical management alternatives are considered, considering that the product conditioning tasks from the harvest such as: classification, drying, fermentation and more employment techniques become strategic activities to meet the market requirements, manifested in various rules governing marketing, especially external. Keywords: Economies, biodiversity, comparative advantages, quality, UPAS (s), production systems, conditioning techniques, standards, external markets.